Authentic supplementary materials in an English language classroom: perceptions of trainee teachers and students / Nur Afifah Addenan - Addenan, Nur Afifah (2009)
ESL teachers are constantly trying to find new ways in catering students' needs for an effective language learning. There are a variety of available textbooks for ESL teaching now. However, the material may not be enough to encourage students' understanding and interest towards learning the language. It is important for teachers to consider supplementary materials for their classroom instruction. Supplementary materials may help teachers in giving new experience in their teaching as well as students' encounter with variety of language use. Authentic material is one of the alternatives for teachers to provide students with a whole new perspective in language learning. Authentic materials have been supported in many areas of teaching. Students need to expose themselves to different kinds of materials that will put benefit in their learning. Therefore, this study will focus on teachers and students' perceptions towards the use of authentic materials in an English classroom. This study will help teachers in selecting the suitable materials for their classroom instruction. It will also reveal the advantages and disadvantages carried from authentic materials. Understanding the quality of materials, this study will also offer teachers the solution for the problems faced upon the use of authentic materials.